Rhetorical Structure of Method Section: A Comparative Study on Research Articles Written by Cambodian Authors Published in National and International Journals - Sovann, Ly; Safnil, Safnil; Syafryadin, Syafryadin (English Education: Jurnal Tadris Bahasa Inggris, 2022)
Method section of research articles defined as a crucial part among several sections. This study employed an analytical framework of method sections by adopting from Zhang and Wannaruk (2016) adjusting from Pho's (2008a). There were 15 research articles published in International Journal and 15 others published in Cambodian National Journal selected as the sample for the study. Three vital research questions were established to investigate this analysis comprising (1) to find out on moves structure in Method sections of RAs written by Cambodian authors published in national journal; (2) the same moves structure in Method section of RAs published in international journals; and (3) the differences of both move structure in Method sections of RAs in national and international journals. Three moves in method section were used in the study such as: Move1 on Describing Research Design; Move2 on Describing Data Collection procedures; and Move3 on Describing Data Analysis. The results stated that all these three moves were found as conventional moves in International Journal while optional moves were found in National Journal. Almost the same results on steps in move2 from the analysis except step2 which was found as obligatory in the International Journal. One step in move3 and five steps in move2 were found as the same status. There were only three optional steps found in International while there were five steps and three moves were found as optional steps and moves. This analysis suggested that Cambodian National Journal should provide clear distinction in writing method sections by introducing specific model of moves and steps to write a qualify method for a research. Future researcher should study rhetorical analysis of move structure in method section in the same filed but the samples should be selected from new published research articles and increased the number of research articles for the analysis.